2023
DOI: 10.1111/jgs.18611
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging mediates the associations of unhealthy lifestyles with cardiovascular disease, cancer, and mortality

Xueqin Li,
Xingqi Cao,
Jingyun Zhang
et al.

Abstract: BackgroundWith two well‐validated aging measures capturing mortality and morbidity risk, this study examined whether and to what extent aging mediates the associations of unhealthy lifestyles with adverse health outcomes.MethodsData were from 405,944 adults (40–69 years) from UK Biobank (UKB) and 9972 adults (20–84 years) from the US National Health and Nutrition Examination Survey (NHANES). An unhealthy lifestyles score (range: 0–5) was constructed based on five factors (smoking, drinking, physical inactivity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Aging is a general biological phenomenon that affects all human beings and is characterized by a progressive loss of physiological integrity, leading to functional decline and increased risk of chronic ailments and death [5] . The population of older persons is one of the fastest-growing age groups, representing 10% of the global population in 2022 and expected to reach 16% by 2050, exceeding more than twice the number of children under the age of five and approximately the same as the number of children under the age of twelve [6] . Although aging is a natural and inevitable process, accelerated aging (i.e., when biological age exceeds chronological age) is a primary risk factor for chronic illness and mortality [7] .…”
Section: Human Aging: Hallmarks and Implicationsmentioning
confidence: 99%
“…Aging is a general biological phenomenon that affects all human beings and is characterized by a progressive loss of physiological integrity, leading to functional decline and increased risk of chronic ailments and death [5] . The population of older persons is one of the fastest-growing age groups, representing 10% of the global population in 2022 and expected to reach 16% by 2050, exceeding more than twice the number of children under the age of five and approximately the same as the number of children under the age of twelve [6] . Although aging is a natural and inevitable process, accelerated aging (i.e., when biological age exceeds chronological age) is a primary risk factor for chronic illness and mortality [7] .…”
Section: Human Aging: Hallmarks and Implicationsmentioning
confidence: 99%
“…Studies have shown that accelerated aging is a significant risk factor for numerous diseases, including heart disease [ 6 ], chronic respiratory disease [ 7 ], depression [ 8 ], cancer [ 2 ], and others. Li et al discovered that accelerated aging could mediate the associations between unhealthy lifestyles and the risk of cardiovascular disease, cancer, and all-cause mortality [ 9 ]. Additionally, accelerated aging may result in a deterioration of physiological functions, such as impaired lung function [ 10 ].…”
Section: Introductionmentioning
confidence: 99%